Geography limits island small‐scale fishery production. Issue 2 (30th October 2017) - Eriksson, Hampus; Friedman, Kim; Amos, Moses; Bertram, Ian; Pakoa, Kalo; Fisher, Rebecca; Andrew, Neil
Abstract: Interacting social and ecological processes shape productivity and sustainability of island small‐scale fisheries (SSF). Understanding limits to productivity through historical catches help frame future expectations and management strategies, but SSF are dispersed and unaccounted, so long‐term standardized data are largely absent for such analyses. We analysed 40 years of trade statistics of a SSF product that enter international markets (sea cucumber) from 14 Pacific Island Countries and Territories (PICT) against response variables to test predictors of fishery production: (i) scale, (ii) productivity and (iii) socio‐economics. Combined production in PICT peaked over 20 years ago, driven by exploitation trends in Melanesia that accounted for 90% of all production since 1971. The size of island fisheries (as measured by total exports), and the duration and magnitude of fishery booms were most influenced by ungovernable environmental variables, in particular land area. The large and high islands of Melanesia sustained larger booms over longer periods than atoll nations. We hypothesize that land area is a proxy for land‐based nutrient availability and habitat diversity, and therefore the productivity of the shallow water areas where SSF are operating. PICT need to tailor management based on the intrinsic productivity of shallow inshore habitats: harvests from atoll nations will need to be smaller per unit area than at the high islands. Particularly countries with low productivity fisheries must consider the crucial economic "safety nets" that export SSF make up for dispersed island populations and incorporate them into broader development and island resilience strategies.